(untitled) (Journal of Philosophy Culture and Political Science, 2023)
The article tells about the manuscripts of the work of the great thinker, of the academic-Enciclopedist Abu Nasr al-Farabi (260-339 hijri/870-950 miladi), stored in the archival funds and libraries of Turkey, and also gives a scientific description of some of his manuscripts. And the manuscript versions of the work of the scientist are mentioned, stored under different names in the libraries and manuscript funds of Turkey, and the copy makers of the manuscripts and the dates of their copying, the type of handwriting and the types of seals printed in the manuscripts are indicated. Despite the fact that the great scientist was from the ancient Kazakh steppe - from Otyrar, his scientific life took place on the edge. And the article emphasizes the role and importance of Turkey’s manuscript funds in returning to Kazakhstan the written heritage of a scientist which has been in a closed state for many centuries. Duiring the writing the article were used the materials from the electronic library of Museum of Topkapi Palace Library, Hagia Sophia, Suleimani Library, Esad Efendi Kütüphanesi, Izmir Halk Kütüphanesi, Fatih Kütüphanesi, Beyazıt Devlet Kütüphanesi, Jarullah Kütüphanesi Şehit Ali Paşa Kütüphanesi which are located in Turkey. Based on the fundamental changes in the Farabi Studies in Kazakhstan in recent years (to form new directions in the study of the heritage of al-Farabi, the definition of manuscripts of the scientist’s works, the collection of found manuscripts and their translation from the original and reprint, define scientific terms, draw new conclusions, etc.) research were used historical-comparative, classification methods. Key words: heritage of Al-Farabi, Turkey’s manuscript funds manuscript, scientific description, the electronic library.